GAMBARAN DISTRIBUSI FAKTOR RISIKO PADA PENDERITA ULKUS DIABETIKA DI KLINIK KITAMURA PKU MUHAMMADIYAH PONTIANAK - ., Meilani Ayu Lestari (Jurnal Mahasiswa PSPD FK Universitas Tanjungpura, 2013)
Background. Diabetic ulcer is one of diabetes mellitus chronic complicationssuch as open wound on skins surface which can along with death of tissue. Theprevalence of patients with diabetic ulcers in Indonesia was about 15% with 30%amputation rate, mortality rate was 32% and become the most cause of hospitaltreatment with 80% rate. Objective. This studys aim was to find out the riskfactors in patients with diabetic ulcers in Kitamura Clinic PKU MuhammadiyahPontianak in the period of October 1st, 2011 - March 31st, 2012. Method. Thisresearch was descriptive research with cross-sectional approach. Sample whichused in this study was 60 people. Data was obtained through questionnaires andmedical records of patients. Result. Largest group of sample was 29 people whoabove 60 years old, most patients who suffer DM for more than 10 years as manyas 37 people, a history of hypertension as many as 41 people, 32 people with nohistory of smoking, 57 people with less physical exercise, 54 people who hadobese history, 48 people who did not change their diet, 43 people with a historyof uncontrolled blood glucose, and patients with poor foot treatment and improperfootgear usage as many as 59 people. Conclusion. The most common agegroup of patient with Diabetic Ulcer in Kitamura Clinic were people with age morethan 60 years (48.33%), suffering DM for more than 10 years (61.67%), historyof hypertension (68.33%), non-smokers (53.33%), less physical exercise (95%),history of obesity (90%), history of unchanged diet (80%), history of uncontrolledblood glucose (71.67%), a history of poor foot treatment (98.33%) and history ofimproper footgear usage (98.33).Keywords : Risk Factors, Diabetic Ulcer, History of uncontrolled blood glucose.